Socio-economic impact analysis of livestock disease control programmes with special reference to ticks and tick-borne diseases. - Randela, R. (University of Pretoria, 2000)
The outbreak of East Coast fever in the beginning of the century lead to the introduction of the plunge dip system to control the disease. This approach focused on eradicating the vectors (i .e. ticks) that transmitted the disease. The successful eradication of the disease in 1954 was mainly through the intensive use of acaricides. The fundamental objectives of this study is to detennine whether there is continued justification for controlling ticks and tick-borne diseases through dipping, as well as identifying the impact of tick control to the rural household. The study was conducted in two veterinary zones located in the Venda region of the Northern Province, namely the Yellow Line and the Open area. A sample of 125 respondents was taken from livestock fanners in the selected areas within the aforementioned zones. Data was accumulated by the use of a structured questionnaire, observations, as well as discussions with fanners. III Cattle dipping is perfonned to achieve both the economic, cultural and the social role with the majority of respondents (97%) fanning with cattle both for commercial and subsistence purposes. The value of cattle has been estimated to be Rl 152. A number of criteria have been used to estimate this value. These are the value of sales, milk, draught power and manure, and are quantified using the replacement value method. Eleven percent of the respondents expressed some dissatisfaction with the classical tick control method (plunge dip). The development of tick resistance to successive acaricide compounds is a major problem stated by 79% of the dissatisfied fanners . As a result, most of the respondents (61 %) supplement dipping with either modem or traditional tick control measures such as hand picking. The surveys amongst rural households show a 3% mortality rate in spite of the existence of the programme. It is estimated that the mortality rate would have been 4% without the control programme. Cost-benefit analysis revealed a benefit-cost ratio of 0.8 (i.e.<l) indicating that the control of ticks and tick-borne diseases by the government is not economically justified. However, because of the economic nature of the service it provides (public good), the dipping of cattle still deserves government support. In addition, the provision of tick control services by the government leads to a socially optimal level of supply. The sensitivity analysis gives the benefit-cost ratio of 1.2 when the mortality rate is assumed to would have been 10% without the control programme. The results of both the logistic regression model and the multivariate regression analysis revealed that the structure of production (e.g. breed of cattle kept), as well as human resource factors (e.g. educational qualification) influences the demand for tick control service and fanners' willingness-to-pay for such a service significantly. In addition, there is also a slight indication of regional differences with regard to the demand for dipping and willingness-to-pay for the service by fanners. The manner in which cattle dipping should be continued by the government, however, needs some alterations. The currently envisioned tick control strategy is based on integrated tick management system where acaricides will be strategically applied. This IV strategy will reduce the costs of tick control thereby improving the benefit-cost ratio. However, there is no easy and straightforward solution on the frequency of cattle dipping. A multi-disciplinary study needs to be conducted to ensure an optimal tick control strategy compatible with the needs of the resource poor farmers. v